2005
DOI: 10.1016/j.jacc.2004.12.050
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia is an important predictor of impaired coronary flow before reperfusion therapy in ST-segment elevation myocardial infarction

Abstract: Hyperglycemia in patients with STEMI is an important predictor of impaired epicardial flow before reperfusion therapy has been initiated. Investigation of methods improving coronary flow before primary PCI in these patients is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
3
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(82 citation statements)
references
References 13 publications
3
72
3
4
Order By: Relevance
“…Acute hyperglycemia is associated with several adverse effects that contribute to poor outcome in STEMI. They include increased oxidative stress, increased cytokine activation, Inflammatory response, endothelial dysfunction and impaired microcirculatory function as manifested by post-PCI no-reflow and impaired ischemic preconditioning [4,[21][22][23][24][25]. Hyperglycemia has also been shown to have several prothrombotic effects and enhanced platelet activation with subsequent increased risk for thrombotic events [26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Acute hyperglycemia is associated with several adverse effects that contribute to poor outcome in STEMI. They include increased oxidative stress, increased cytokine activation, Inflammatory response, endothelial dysfunction and impaired microcirculatory function as manifested by post-PCI no-reflow and impaired ischemic preconditioning [4,[21][22][23][24][25]. Hyperglycemia has also been shown to have several prothrombotic effects and enhanced platelet activation with subsequent increased risk for thrombotic events [26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…35,39 Hyperglycaemia in patients with STEMI is an important predictor of impaired epicardial flow before reperfusion therapy has been initiated. 40 In a series of 460 consecutive STEMI patients, TIMI flow grade 3 before primary PCI was observed less often in patients with hyperglycaemia (> 7.8 mmol/L) compared to patients without hyperglycaemia (12% vs. 28%, p<0.001). After adjustment for differences in baseline variables, hyperglycaemia was a strong predictor of absence of reperfusion before primary PCI (odds ratio 2.6, 95% CI 1.5 to 4.5).…”
Section: Why Do Reperfusion Therapies Fail In Diabetics With Stemi?mentioning
confidence: 96%
“…Recent study of Mansour et al [7] confirmed that increased BG level (≥ 7.8 mmol/L) is an unfavorable prognostic factor also in patients with ACS. Hyperglycemia in these patients leads to higher levels of cardiac necrosis markers and lower left ventricular ejection fraction [9,22]. It also leads to increased endothelial dysfunction, hypercoagulability and impaired fibrinolysis [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of admission hyperglycemia (glucose levels ≥ 7.8 mmol/L) in different epidemiological studies ranges from 51% to > 58% of patients hospitalized with AMI [8]. Increased glucose level on admission is an independent factor of more impaired initial flow in the infarct-related artery and occurrence of no-reflow phenomenon [9]. In addition, patients with hyperglycemia have higher Killip class, a larger infarct and worse left ventricular (LV) function [10].…”
Section: Introductionmentioning
confidence: 99%